Determinants of Accounting Conservatism in Infrastructure Companies Listed on the Indonesia Stock Exchange - Tomi Sutoro (Journal of Social Research, 2026)
The research aims to test and analyze the effect of the investment opportunity set, financial distress, and litigation risk on accounting conservatism. This form of research uses quantitative methods with statistical tools like Eviews12. The population of this study were all infrastructure sector companies listed on the Indonesia Stock Exchange, totaling 69 companies. The sampling method used purposive sampling, which amounted to 46 companies. Data analysis techniques in the form of descriptive statistics, model selection, classical assumption tests, panel regression analysis, and hypothesis testing results showed that investment opportunity set, financial distress, and litigation risk have a positive and significant effect on accounting conservatism in the infrastructure sector companies on the Indonesia Stock Exchange. The adjusted R square results show a value of 27.29%, while the remaining 72.71% is explained by other independent variable factors that affect accounting conservatism. In short, it can be concluded that the higher the IOS, financial distress condition, and litigation risk, the higher the level of accounting conservatism applied by infrastructure companies. This research provides practical implications for company management, investors, and regulators in assessing financial reporting practices in the infrastructure sector.